Key Performance Indicators for Sustainable Management A Compendium Based on the "Balanced Scorecard Approach" - Krause, Hans-Ulrich (De Gruyter Oldenbourg, 2019)
Key Performance Indicators (KPIs) have become a regular and useful tool for measuring business performance everywhere. The KPIs not only help in strategic planning but also in managing operative business world over. The KPIs in the book are organized according to the Balanced Scorecard (BSC) approach, which emphasizes the importance of using both financial and non-financial information to remain competitive in the modern world. We proudly place on record the fact that our book is the first of its kind and provides for a complete analysis of KPIs under financial, customer, process and human resource/innovation perspectives. The book is a major contribution towards achieving sustainable growth as a competitive advantage. It also emphasizes the importance of social acceptance and environmental impact of the business activity. The compendium provides over 170 KPIs in a compact form. It delivers simple definitions, easy to calculate formulae, possible interpretations and useful suggestions towards an efficient and effective implementation of KPIs as controlling instruments.